2022
DOI: 10.1115/1.4053417
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Hip Prosthesis Using Different Biocompatible Alloys

Abstract: In the present paper, a three-dimensional finite element model of the Charnley implant has been developed to analyze the stress–strain distribution and deformation over the stem prosthesis. Patient-specific dynamic forces have been considered for the analytical evaluation using commercial finite element code. The impact of each dynamic activity has been analyzed separately using six different biocompatible alloy materials made of titanium and cobalt-chromium. Mechanical parameters have been evaluated to envisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The gait loading in the current study, as shown in Figure 3 only considers the vertical force without the range of motion as was conducted by Jamari et al [ 35 ]. This is because the finite element model of hard-on-hard bearings currently uses 2D axisymmetric, making it impossible to adopt triaxial motion during gait loading [ 37 ]. For the convenience of the computational simulation procedures, the gait loading is divided into 32 phases as referred from previous study [ 27 , 34 , 38 ] consisting of two main groups, namely the stance phase (60% of gait loading) and the swing phase (40% of gait loading) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The gait loading in the current study, as shown in Figure 3 only considers the vertical force without the range of motion as was conducted by Jamari et al [ 35 ]. This is because the finite element model of hard-on-hard bearings currently uses 2D axisymmetric, making it impossible to adopt triaxial motion during gait loading [ 37 ]. For the convenience of the computational simulation procedures, the gait loading is divided into 32 phases as referred from previous study [ 27 , 34 , 38 ] consisting of two main groups, namely the stance phase (60% of gait loading) and the swing phase (40% of gait loading) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FEM technique [27][28][29][30] is a fast and efficient technique widely employed for solving complex shape analysis. Additionally, these techniques are used to assist and optimize the design of hip prostheses and provide an understanding of their mechanical behavior under multiple loading constraints [31][32][33]. The finite element model of the prosthesis assembly is depicted in Figure 1.…”
Section: Materials and Methods Finite Element Modelingmentioning
confidence: 99%
“…To validate the computational model, the stresses induced and displacements during the walking cycle are compared with previously published literature [39]. Only the stem is used to validate the computational model before furthering the analysis of the complete hip implant.…”
Section: Validation Of Computational Modelmentioning
confidence: 99%
“…Only the stem is used to validate the computational model before furthering the analysis of the complete hip implant. Joshi et al [39] have used an implant stem model considering six different biocompatible alloy materials. For the validation of the current work, we used materials like Ti-6Al-4V and Co Cr alloy for the stems.…”
Section: Validation Of Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation